2021
DOI: 10.3390/ijms22073529
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Identification and Characterization of FCS-Like Zinc Finger (FLZ) Family Genes in Maize (Zea mays) and Functional Analysis of ZmFLZ25 in Plant Abscisic Acid Response

Abstract: FCS-like zinc finger family proteins (FLZs), a class of plant-specific scaffold of SnRK1 complex, are involved in the regulation of various aspects of plant growth and stress responses. Most information of FLZ family genes was obtained from the studies in Arabidopsis thaliana, whereas little is known about the potential functions of FLZs in crop plants. In this study, 37 maize FLZ (ZmFLZ) genes were identified to be asymmetrically distributed on 10 chromosomes and can be divided into three subfamilies. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The essential role of SnRK1A in rice submergence tolerance has been well established (Lu et al 2007 ; Lee et al 2009 ; Cho et al 2012 ). Previous studies showed that FLZs could interact with the subunits of the SnRK1 kinase complex in Arabidopsis and maize (Arabidopsis Interactome Mapping Consortium 2011 ; Nietzsche et al 2014 , 2016 ; Jamsheer et al 2018a , b ; Chen et al 2021 ). To see whether OsFLZs can also interact with SnRK1A to regulate rice response to submergence stress, we selected the above eight representative OsFLZ genes to perform a yeast two-hybrid assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The essential role of SnRK1A in rice submergence tolerance has been well established (Lu et al 2007 ; Lee et al 2009 ; Cho et al 2012 ). Previous studies showed that FLZs could interact with the subunits of the SnRK1 kinase complex in Arabidopsis and maize (Arabidopsis Interactome Mapping Consortium 2011 ; Nietzsche et al 2014 , 2016 ; Jamsheer et al 2018a , b ; Chen et al 2021 ). To see whether OsFLZs can also interact with SnRK1A to regulate rice response to submergence stress, we selected the above eight representative OsFLZ genes to perform a yeast two-hybrid assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, 757 FLZ proteins have been identified from 41 plant genomes including 29 members in rice through genome-wide identification, and they were plant-specific zinc finger proteins involved in protein–protein interaction (Jamsheer and Laxmi 2014 ; Jamsheer et al 2015 ). Until now, most information on FLZ family genes were obtained from studies in Arabidopsis and maize (He and Gan 2004 ; Chen et al 2013 , 2021 ; Hou et al 2013 ; Jamsheer and Laxmi 2014 , 2015 ; Nietzsche et al 2014 , 2016 ; Jamsheer et al 2018a , b ), and FLZ proteins in other plants have not yet been characterized. In the present study, we have provide the gene and protein attributes, and phylogenetic relationships among the 29 OsFLZ proteins (Additional file 1 : Table S1, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the architecture of AMPK, SnRK1 exhibits a highly conserved heterotrimeric structure comprising a catalytic a subunit (two isoforms in Arabidopsis, KIN10 and KIN11) and regulatory b and c subunits [57,58]. FCS-like zinc finger proteins (FLZs) are identified as the plant-specific adaptors of SnRK1, which might be involved in the regulation of TOR signalling through affecting the interaction between SnRK1 and RAPTOR in plants [59][60][61].…”
Section: Regulation Of Plant Autophagy By Phosphorylationmentioning
confidence: 99%